Antipsychotic treatment is associated with inflammatory and metabolic biomarkers alterations among first‐episode psychosis patients: A 7‐month follow‐up study. Issue 1 (18th July 2017) - Balõtšev, Roman; Haring, Liina; Koido, Kati; Leping, Vambola; Kriisa, Kärt; Zilmer, Mihkel; Vasar, Veiko; Piir, Anneli; Lang, Aavo; Vasar, Eero
Abstract : Aim: Second‐generation antipsychotics are commonly used to treat schizophrenia, but may cause metabolic syndrome (MetS) in a subset of patients. The mechanisms of antipsychotic‐related metabolic changes remain to be established, especially in first‐episode psychosis (FEP) patients. Methods: In the present study, we used a chip technology to measure metabolic (C‐peptide, insulin, leptin, adiponectin and resistin) and inflammatory biomarkers (ferritin, interleukin‐6, interleukin‐1α, tumour necrosis factor‐α and plasminogen activator inhibitor‐1) in the serum samples of a population of FEP patients before and after 7 months of antipsychotic drug treatment, compared to control subjects (CS). Results: The comparison of these markers in antipsychotic‐naïve FEP patients ( N = 38) and CS ( N = 37) revealed significantly higher levels of ferritin ( P = .004), and resistin ( P = .03) and lower level of leptin ( P = .03) among FEP patients group. Seven months of antipsychotic drug treatment in patients ( N = 36) ameliorated clinical symptoms, but increased significantly body mass index (BMI; P = .002) and these changes were accompanied by increased levels of C‐peptide ( P = .03) and leptin ( P = .02), as well as decreased level of adiponectin ( P = .01). Conclusions: Seven months of antipsychotic drug treatment suppressed the clinical symptoms of psychosis whereas caused imbalance in metabolic biomarkers and increased BMI. These findings provide insight into antipsychotic‐induced MetS and refer to problems in insulin processing already present in the early stage of the chronic psychotic disorder.